Faculty Self- and Needs Assessment of Preparedness for Integrating Active Learning Based on Medina's Conceptual Framework. (October 2021) - Joseph, Merlyn; Farris, Charlotte; Martinez, Mardoqueo; Demps, Elaine; Hernández-Muñoz, José J.
BACKGROUND: Active learning (AL) is recognized as a valuable learning strategy. OBJECTIVE: Using a conceptual framework, the objective of this study was to conduct a faculty self- and needs assessment to determine the extent to which the faculty at one college of pharmacy perceived they already carried out AL, describe faculty challenges, and evaluate faculty examples of AL techniques. METHODS: A 19-question survey was administered in July 2017 to all 50 college faculty. Survey question types included multiple-choice single- or multiple-answer questions and open-ended questions. For validity, Medina's conceptual framework of 4 key elements for the effective administration of AL was used. For reliability, the draft survey questions were reviewed multiple times and revised accordingly. RESULTS: Thirty-five faculty members, 70%, completed the survey in full. The majority of the faculty perceived that they carried out 3 of the 4 key elements during lectures: activate prior knowledge (74%), involve the majority of students (89%), and provide feedback (91%). However, only 37% stated they promoted metacognition, another key element. Our qualitative analysis identified (1) faculty had misconceptions about most of Medina's conceptual framework elements, (2) challenges to AL implementation included: need for more technology training, perception that AL requires cutting course material, beliefs that AL does not work, and fear of poor evaluations with AL implementation, and (3) suggestions to improve AL included: faculty development, training students on the importance of AL, and integrating AL throughout the curriculum. CONCLUSIONS: Although most faculties indicated they integrated AL in their teaching, faculty misconceptions, and beliefs suggest the need for long-term faculty and organizational development using strategies aligned with or seeking to change the beliefs of the faculty and college system.